Tahap kesedaran kerjaya pelajar tingkatan enam di daerah Kluang dalam pemilihan kerjaya - Tan, Tai (2013)
Career awareness is the key to students in improving themselves and improve the world in the face of an increasingly challenging career. Therefore, this study aimed to identify the level of career awareness of form six students in career selection . There are four factors, that were gender, race, occupation of father and students’ MCE results have been study. Respondents consist of Form Six students from seven public schools that operate pre- university program in Kluang District. The sample consisted of 142 respondents selected randomly. This study is descriptive and questionnaire as research instrument. Analysis of the data using the Statistical Package for Social Sciences (SPSS) version 16.0 for a percentage, mean, standard deviation, ANOVA and t-test. Findings indicated that students in career awareness prepare for the career environment is high (mean score = 3.94) . The study also shows that there is no significant relationship between the four factors studied were sex, race, occupation of father and MCE results on students' career awareness. The proposed study is to identify the key variables that are significantly correlated with career choices.